2015
DOI: 10.1590/0103-9016-2014-0155
|View full text |Cite
|
Sign up to set email alerts
|

Methane production of two roughage and total mixed ration as influenced by cellulase and xylanase enzyme addition

Abstract: In recent decades supplementation of animal feeds with exogenous fibrolytic enzymes has substantially improved digestibility and animal performance. However, information related to associated methane production is limited and inconsistent. This study evaluated the effect of cellulase and xylanase enzymes on in vitro methane production of Eragrostis curvula hay, maize (Zea mays) stover and a total mixed ration (TMR) at seven levels of the two enzymes.Feed samples were incubated for 2, 12, 24 and 48 h in an in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
4
0
1
Order By: Relevance
“…Interestingly, higher abundance of Succinivibrio , which was the reason of low methane production from hindgut of Tammar wallabies ( Pope, 2011 ), was also observed in the inoculum incubated with cassava residues. This was also consistent with the conclusion that the ruminal methane production is always lower by feeding low fiber feedstuffs to ruminants ( Gemeda and Hassen, 2015 ).…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, higher abundance of Succinivibrio , which was the reason of low methane production from hindgut of Tammar wallabies ( Pope, 2011 ), was also observed in the inoculum incubated with cassava residues. This was also consistent with the conclusion that the ruminal methane production is always lower by feeding low fiber feedstuffs to ruminants ( Gemeda and Hassen, 2015 ).…”
Section: Discussionsupporting
confidence: 91%
“…Experiment 1-in vitro fermentation: The technique of in vitro batch culture in 100 ml serum bottle was performed (3 runs) as per Gemeda and Hassen (2015). The enzymatic supplementation was performed with 2 different methods according to the enzymes form.…”
Section: Methodsmentioning
confidence: 99%
“…The higher CH 4 production (g/kg DMI) reported in Table 2 for Treatments 1 and 2 could be due to the associated higher concentrations of cell wall components (NDF and ADF) and lower concentrations of CP and NFC compared to T 3 and T 4. Gemeda and Hassen (2015) reported a negative correlation between in vitro CH 4 production and the NFC, CP and ADIN concentrations in feed samples. These authors also reported a positive correlation between forage fibre concentration and in vitro CH 4 production.…”
Section: Dry Matter Intake Digestion and Methane Productionmentioning
confidence: 98%